Collaborating Around Digital Tabletops: Children’s Physical Strategies From India, The UK And Finland - Jamil, Izdihar; Montero, Calkin Suero; Perry, Mark; O'Hara, Kenton; Karnik, Abhijit; Pihlainen, Kaisa; Marshall, Mark T.; Jha, Swathi; Gupta, Sanjay; Subramanian, Sriram (2018 ACM Conference on Human Factors in Computing Systems (CHI), 2017)
We present a study of children collaborating around interactive tabletops in three different countries: India, the United Kingdom and Finland. Our data highlights the key distinctive physical strategies used by children when performing collaborative tasks during this study. Children in India employ dynamic positioning with frequent physical contact and simultaneous object movement. Children in the UK tend to prefer static positioning with minimal physical contact and simultaneous object movement. Children in Finland use a mixture of dynamic and static positioning with minimal physical contact and object movement. Our findings indicate the importance of understanding collaboration strategies and behaviours when designing and deploying interactive tabletops in heterogeneous educational environments. We conclude with a discussion on how designers of tabletops for schools can provide opportunities for children in different countries to define and shape their own collaboration strategies for small group learning that take into account their different classroom practices.